2018
DOI: 10.1007/s11010-018-3369-x
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine improved left ventricular function and pressure overload-induced cardiomyocyte apoptosis in a transverse aortic constriction mouse model

Abstract: This study aimed to investigate the effects and molecular mechanisms of ivabradine in preventing cardiac hypertrophy in an established transverse aortic constriction (TAC) mouse model. A total of 56 male C57BL/6 mice were randomly assigned into the following seven groups (8 mice per group): sham, TAC model, Iva-10 (10 mg/kg/day ivabradine), Iva-20 (20 mg/kg/day ivabradine), Iva-40 (40 mg/kg/day ivabradine), Iva-80 (80 mg/kg/day ivabradine), and Rap (rapamycin, a positive control). Echocardiography and left ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Cardiomyocytes apoptosis increases when the heart is subjected to pressure overload or when cardiomyocytes are stimulated by Ang II (Yang et al, 2012;Yu, Hu, Li, Wang, & Chen, 2018). Galangin has been shown to modulate cell apoptosis (Tomar et al, 2017) (a key role in the transcription of profibrotic genes).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocytes apoptosis increases when the heart is subjected to pressure overload or when cardiomyocytes are stimulated by Ang II (Yang et al, 2012;Yu, Hu, Li, Wang, & Chen, 2018). Galangin has been shown to modulate cell apoptosis (Tomar et al, 2017) (a key role in the transcription of profibrotic genes).…”
Section: Discussionmentioning
confidence: 99%
“…Heart disease animal models play an important role in studying these remodeling processes as well as in preclinical studies. The validity and accuracy of animal models are necessary for the mechanism study of HF and for new drug development as well (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the effect of ivabradine on HFpEF, we treated mice at 4-weeks post-TAC with low-dose (10 mg/kg/d) [ 34 , 35 ] or high-dose (20 mg/kg/d) [ 34 , 35 ] ivabradine for another 4 weeks. We found that high-dose but not low-dose ivabradine significantly inhibited pressure overload-induced cardiac hypertrophy by reducing the cross-sectional areas of ventricular cardiomyocytes and the ratio of heart weight to tibial length (Figures 2(a) – 2(c) ).…”
Section: Resultsmentioning
confidence: 99%